2013
DOI: 10.1186/1472-6831-13-60
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and psychosocial predictors of dental healthcare use among Brazilian preschool children

Abstract: BackgroundDisparities in utilization of oral healthcare services have been attributed to socioeconomic and individual behavioral factors. Parents’ socioeconomic status, demographics, schooling, and perceptions of oral health may influence their children’s use of dental services. This cross-sectional study assessed the relationships between socioeconomic and psychosocial factors and the utilization of dental health services by children aged 1–5 years.MethodsData were collected through clinical exams and a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
95
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 18 publications
18
95
1
8
Order By: Relevance
“…25 However, previous studies showed that dental care utilization by preschool children is low and is associated with socioeconomic factors. 3,4,5,26 In our study, socioeconomic factors were related to the use of dental care, as reported by other authors. 3,4,5,26 The current study considered household income and parents' schooling as proxies for socioeconomic status, which were identified as individual determinants for the outcome.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…25 However, previous studies showed that dental care utilization by preschool children is low and is associated with socioeconomic factors. 3,4,5,26 In our study, socioeconomic factors were related to the use of dental care, as reported by other authors. 3,4,5,26 The current study considered household income and parents' schooling as proxies for socioeconomic status, which were identified as individual determinants for the outcome.…”
Section: Discussionsupporting
confidence: 84%
“…3,4,5,26 In our study, socioeconomic factors were related to the use of dental care, as reported by other authors. 3,4,5,26 The current study considered household income and parents' schooling as proxies for socioeconomic status, which were identified as individual determinants for the outcome. Notwithstanding, only mother's schooling was fitted into the final model after adjustment for contextual variables.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations